Terracing and ridge planting enhances soil organic carbon stability on water-eroded farmland slopes in Northeast China - Zhu Zhengqing; Mark Henderson; Gu Ruiting; Zhang Zhi; Zheng Xiaotong; Gong Xiaojing; Li Shang; Zhang Jiaqi; Liu Binhui (CATENA, 2026)

Study on the degradation of tetracycline in aqueous solution using MIL-53(Fe) generated by needle–plate pulsed discharge - Ruiting Jian; Manli He; Jiushan Cheng; Bowen Liu; Zhengduo Wang; Zhongwei Liu (Journal of Environmental Chemical Engineering, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Chemical distance outweighs phylogeny in VOC-mediated cross-species plant defense communication - Chaonan Wang; Danfeng Liu; Xiao Xu; Mingjun Gao; Jiawei Wang; Jieren Jin; Yupeng Geng; Ruiting Ju; Yi Wang; Xiaoming Lu; Jihua Wu; Bo Li (Science China Life Sciences, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

SIRT6 inhibits intermittent hypoxia-induced lung injury by stabilizing NRF2 - Ruiting Qin; Zhijuan Liu; Ran Li; Yongxia Li; Yuan Yang; Li Ai (Tissue and Cell, 2026)

Climate-driven dynamics of surface water temperature and its coupled responses to lake heatwaves and cyanobacterial blooms in Lake Taihu - Lei Sun; Ruiting Xu; Yakun Feng; Haozhang Dai; Menglin Yuan; Chenhui Wu; Hao Wang; Ya Liu; Cuiling Jiang (Journal of Environmental Management, 2026)

Why nanofiltration performance declines in real textile wastewater: Roles of organic complexity, salinity, and fouling - Hai Tang; Qiyao Cheng; Ruiting Wen; Shasha Liu; Haiao Zeng; Jianquan Luo (Desalination, 2026)

Tempol suppresses ferroptosis and relieves chronic intermittent hypoxia-induced lung injury through the inhibition of TLR4 and activation of the Nrf2/GSH axis - Ran Li; Ruiting Qin; Zhijuan Liu; Xiaojie He; Dan Li; Li Ai (Tissue and Cell, 2026)

Deciphering the impacts of multi-source materials on semi-continuous anaerobic digestion of food waste: performance enhancement and mechanism analysis - Yongdong Chen; Ruiting Zhu; Fang Liu; Xiuxia Zhang; Shi Li; Li Gu; Jiancheng Shu (Journal of Environmental Management, 2026)

Eliminating the asymmetric electrochemistry of zinc electrodes to achieve long-life Zn-MnO2 full cells - Ruiting Guo; Xinzhe Dai; Peiyuan Si; Yubang Fan; Chunhua Han; Chaojiang Niu; Xiong Liu (Chemical Engineering Journal, 2026)

Multi-objective optimization of membrane-based dehumidification system for sustainable museum microclimates - Yilin Liu; Ruiting Wu; Junbao Fan; Lip Huat Saw; Liwen Jin (Building and Environment, 2026)

Astrocytic HMGCR-Mediated Cholesterol Alleviated Parkinson’s Disease Phenotypes by Inhibiting NF-κB Neuroinflammation - Xiaofeng Tian; Qing Liu; Jiacheng Zhang; Huijiao Du; Zhaoran Wei; Linjie Sun; Jiamin Gao; Ruiting Zhao; Lei Wang; Yizhou Zhang (Molecular Neurobiology, 2026)

Construction of built-in electric field in Ru/Vo-NiCo2O4 heterostructure for efficient ethylene glycol oxidation reaction coupled nitrate to ammonia electrolysis - Jingwen Ma; Ruiting Wang; Jinhao Liu; Ying Tian; Junbin Li (Journal of Environmental Chemical Engineering, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Carbon stocks in two temperate Zostera meadows in the Yellow Sea, North China - Ruiting Gu; Sichao Pu; Jianwu Tang; Tingting Liu; Linjing Ren; Shaochun Xu; Shuo Yu; Xiuzhen Li; Ning Zhao (CATENA, 2025)

Enabling kinetics matching in electrocatalytic ammonia synthesis by leveraging spatially-confined Cu/Fe2O3 heterointerfaces to maximize *H supply and utilization - Mengting Liu; Fu Yang; Hongyao Zhao; Xiu Zhong; Ruiting Ni; Kwame Nana Opoku; Zhenxiao Wang; Yangping Zhang; Yanyun Wang; Feng Zeng; Yinlong Zhu; Weidong Shi (Chemical Engineering Journal, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Electron-deficient asymmetric Co centers marry oxygen vacancy for NO3RR: Excellent activity and anion resistance property - Hao Lu; Kwame Nana Opoku; Zhenxiao Wang; Ruiting Ni; Mengting Liu; Yanyun Wang; Yangping Zhang; Chao Yu; Aihua Yuan; Fu Yang; Weidong Shi (Chemical Engineering Journal, 2025)

Ubiquitin-conjugating enzyme E2T confers chemoresistance of colorectal cancer by enhancing the signal propagation of Wnt/β-catenin pathway in an ERK-dependent manner - Bo Liu; Ruiting Liu; Xiaolong Zhang; Lifei Tian; Zeyu Li; Jiao Yu (Chemico-Biological Interactions, 2025)

Halobacillus rhizosphaerae sp. nov., a moderately halophilic bacterium with protease activities isolated from the rhizosphere soil of the mangrove Acanthus ebracteatus - Doudou Yin; Junjie Xie; Rui Liu; Chaodong Song; Ying Liang; Hongzhi Huang; Yihui Huang; Ruiting Long; Naikun Shen; Bing Yan; Hongyan Zhang (Antonie van Leeuwenhoek, 2025)

Gut microbiota modulation by L-Fucose as a strategy to alleviate Ochratoxin A toxicity on primordial follicle formation - Ruiting Wang; Jie Song; Muyu Cai; Yuan Xue; Jing Liu; Ning Zuo; Massimo De Felici; Junjie Wang; Wei Shen; Xiaofeng Sun (Journal of Hazardous Materials, 2024)

Response mechanisms of submerged macrophytes and epiphytic biofilms to single and coexisting per-and poly-fluoroalkyl substances and antibiotics stress - Yakun Feng; Cuiling Jiang; Wei Zhang; Lei Sun; Zequn Fan; Can Lu; Lei Jiang; Ruiting Xu; Ya Liu (Journal of Environmental Chemical Engineering, 2024)

Polymer tethering strategy modified ZIF67 derived cobalt-confined nanocage for norfloxacin degradation: Tailored reactive sites and beneficial local microenvironment - Hongyao Zhao; Enxian Yuan; Kwame Nana Opoku; Mengting Liu; Xiu Zhong; Ruiting Ni; Zhenxiao Wang; Yanyun Wang; Zengjing Guo; Chongchen Wang; Fu Yang (Chemical Engineering Journal, 2024)

Rapid pretreatment strategy to control nanofiltration membrane fouling in recycling of real textile wastewater: Comparison and mechanisms - Hai Tang; Meng Shan; Qiyao Cheng; Ruiting Wen; Shasha Liu; Haiao Zeng; Jingfu Yu; Jianquan Luo (Chemical Engineering Journal, 2024)

Correlation analysis and predicting modeling of pyrolysis gas based on landfill excavated waste pyrolysis characteristics - Yufeng Du; Ruiting Liu; Ping Han; Jin Wang; Feiyong Chen; Guanzhong Chen (Chemosphere, 2024)

Transcriptome Analysis Revealed Potential Immune-Related Genes of Head Kidney in the Yellow Catfish (Pelteobagrus fulvidraco) Challenged with Aeromonas hydrophila - Senhao Jiang; Yuting Lei; Ti Wang; Ruiting Ma; Chunqiang Hou; Qiuning Liu (Fishes, 2024)
Yellow catfish (Pelteobagrus fulvidraco) is an important freshwater fish species in aquaculture. However, as intensive farming has rapidly expanded, infectious diseases caused by various bacteria, such as Aeromonas hydrophila, have also increased. We conducted a transcriptomic analysis of head kidney from P. fulvidraco stimulated by A. hydrophila strain SHOU. A total of 43,249 unigenes with an average length of 1342 bp were obtained following assembly and annotation. By analyzing GO and KEGG enrichment, many differentially expressed genes (DEGs) and pathways related to immunity were identified. Out of the 973 DEGs that were identified, 553 were upregulated and 420 were downregulated. Moreover, KEGG enrichment analysis revealed that the innate immune system, including the TNF signaling pathway, NF-kappa B signaling pathway, and the Toll-like receptor signaling pathway involved in the defense, is activated against infectious response. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis demonstrated that immune response genes were upregulated in response to A. hydrophila stimulation compared to the control. In conclusion, this study provides valuable insights into the immune defense mechanism of P. fulvidraco and sheds light on the host immune genes involved in the response to bacterial infection.

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

An attomolar-level electrochemical DNA biosensor based on target-triggered and entropy-driven catalytic amplification integrated with AuNPs@ZIF-8 nanocomposites for oral cancer overexpressed 1 detection - Jing Li; Qi Jiang; Minhui Chen; Wei Zhang; Ruiting Liu; Jin Huang; Qin Xu (Analytica Chimica Acta, 2024)

Permeability–Friction Relationships for Propped Fractures in Shale - Jiayi Yu; Jiehao Wang; Yan Li; Amr El-Fayoumi; Ruiting Wu; Xiaolong Liu; Peggy Rijken; Andrew P. Rathbun; Derek Elsworth (Rock Mechanics and Rock Engineering, 2023)

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

Effect of Oat Consumption on Blood Pressure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Huihui Xi; Wei Zhou; Yirou Niu; Ruiting Zhu; Saikun Wang; Yingze Guo; Wenqing Liu; Xuance Xiong; Lirong Guo (Journal of the Academy of Nutrition and Dietetics, 2023)

The impacts of urban anthropogenic heat and surface albedo change on boundary layer meteorology and air pollutants in the Beijing-Tianjin-Hebei region - Ruiting Liu; Zhiwei Han; Jiawei Li; Jie Li; Lin Liang; Yunfei Wu (Urban Climate, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution - Haiyan Ding; Ruiting Hou; Yun Li; Beibei Zhang; Baobao Zhao; Kun Liu (Food Additives & Contaminants: Part A, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

The assessment of different vegetation indices for spatial disaggregating of thermal imagery over the humid agricultural region - Kai Liu; Shudong Wang; Xueke Li; Yao Li; Bo Zhang; Ruiting Zhai (International Journal of Remote Sensing, 2020)

Hydrophobin HFBII-4 from Trichoderma asperellum induces antifungal resistance in poplar - Huifang Zhang; Shida Ji; Ruiting Guo; Chang Zhou; Yucheng Wang; Haijuan Fan; Zhihua Liu (Brazilian Journal of Microbiology, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Characterization of the complete chloroplast genome sequence of Cardamine macrophylla (Brassicaceae) - Ting Ren; Yanci Yang; Jiao Wang; Ruiting Zhang; Zhan-Lin Liu (Conservation Genetics Resources, 2018)

Complete chloroplast genome sequence of Pedicularis cheilanthifolia, an alpine plant in China - Ruiting Zhang; Jiao Wang; Kai Han; Ting Ren; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of the Cortusa matthioli subsp. pekinensis (Primulaceae) - Jiao Wang; Ruiting Zhang; Ting Ren; Kai Han; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)